Educational Supervision in an Integrated Islamic Boarding School: Practices, Structural Barriers, and Pathways Toward Teacher Professional Development - Husna Hurin Asma’ Amaniina; Muchammad Eka Mahmud (Tahta Media Group, 2026)
Educational supervision at Ar-Rohmah aims to guarantee and ensure the quality of teacher performance and the implementation of academic, memorization, and extracurricular programs in accordance with established standards. Supervision is conducted through structured procedures, including classroom observations, interviews, unannounced classroom visits, completion of supervision assessment instruments, and evaluation of results documented in the form of videos, photos, and written reports. Supervision also provides opportunities for teachers to consult regarding challenges and difficulties in learning as well as other supporting facilities and resources. The approach used is qualitative, involving interviews, classroom observations, and document analysis using thematic analysis techniques. Findings from the study indicate that the implementation of supervision is not yet optimal because there are no expert supervisors who specialize in the specific fields of the teachers being supervised; consequently, the objectivity of the assessment remains suboptimal, and technical feedback is not sufficiently specific. As a result, improvements in the quality of learning have been less than optimal, and some teachers are still teaching outside their areas of expertise. Nevertheless, supervision continues to be carried out and helps teachers identify shortcomings in their teaching, improve their teaching methods, and enhance innovation in the classroom. Subsequent professional development programs, including regular teacher training, mentoring, and oral and written evaluations, serve as supporting measures implemented by the school. This study emphasises the need to increase the number of supervisors who are experts in their fields, improve the competence of supervisors, and strengthen evaluation mechanisms so that supervision can be conducted objectively and effectively in improving the quality of teachers and learning.